Artistic originality of T. Zhurgenov’s poem «Translator’s Fantasies» - Temirbolat А.Б.; Imangaliyev Б.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article is devoted to the work of a major statesman and public figure Temirbek Karauly Zhurgenov. The object of the study is his only surviving poem “Translator’s Fantasies”. The scientific and practical significance of the study lies in the fact that based on a detailed analysis, the uniqueness and artistic value of this work, the poetic skill of T.K. Zhurgenov, the versatility of his talent are revealed. The article indicates that this poem, written in an ironic form, is characterized by a deep ideological-thematic content. Referring to the image of the translator, T.K. Zhurgenov raises universal problems. He reflects on the spiritual values of society at the beginning of XX century. In the process of analyzing the poem, the peculiarities of the worldview and world perception, the originality of the author’s concept of being by T.K. Zhurgenov are revealed. Tin the article the construction of the work is considered. The poem is analyzed through the prism of the chronotope’s problem. The role and significance of the categories of time and space in the structure and content of the work are determined. Based on the research of the chronotope’s problem, the attitude of the author and the hero to the contemporary reality is determined. In the process of analysis, it is noted that the space-time continuum of T.K. Zhurgenov’s poem is characterized by multidimensionality. In the work the peculiarities of the psychology and value system of the translator are revealed. In the process of analysis, it is indicated that the structure of the poem contains a game that allows deeper understanding of the essence of the problems raised by the author. The value of this research lies in the fact that its results can be used not only in the process of studying T.K. Zhurgenov’s artistic heritage, but also the Kazakh literature of the early XX century, the analysis of poetic works.